The Role of Self-Efficacy on Student Academic Achievement - Chaniva Lailatul Maslakhah; Fadila Dian Wardani; Imtiyaaz Nahdiyant; Sarah Hasanah D Reggia (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2023)
This research aims to determine the importance of self-efficacy for each individual to improve student academic achievement so that students can understand the importance of self-efficacy in developing their own abilities to achieve the maximum possible achievement. This research is motivated by various cases related to students who have low and high self-efficacy which affect academic performance. The research method uses a literature review with a qualitative approach. Data analysis was carried out descriptively qualitatively to find out how important the role of self-efficacy is in student learning achievement. The results of the literature review show that the components of self-efficacy consist of cognition, encouragement, compassion, and decision making in improving student academic achievement. Self-efficacy has the potential to increase the ability to attribute results to success in learning. Students who are considered to have high self-efficacy are able to complete assignments by believing that they are able to formulate plans, get answers quickly, and can solve the problems they face optimally. Conversely, if students do not adhere to the principle of self-efficacy it will be difficult to solve the problems they face. In this article, data was obtained showing that high self-efficacy plays an important role in achieving student academic achievement. Meanwhile, low self-efficacy will not achieve academic achievement.